Estimation of earth structure by satellite gravity analysis of Peninsular Malaysia - Nurul Fairuz Diyana Bahrudin,; Umar Hamzah,; Wan Zuhairi Wan Yaacob, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Power spectral analysis was successfully carried out on satellite gravity data along 10 East-West profiles of about 140 to 320 km length across Peninsular Malaysia beginning from its border with the Straits of Malacca towards the South China Sea coastline. Power spectrum curves obtained clearly indicate the presence of three major slopes corresponding to four type of materials with different dominant densities. Depth curves computed from all these profiles produced three major dominant peaks beginning with the deepest one at about 33 to 42 km, followed by intermediate depth of 18 to 26 km and the shallow peaks at about 3 to 10 km. The shallowest depth is interpreted as representing geological formation such as the Mesozoic and Palaeozoic deposits including the granite intrusion classified as basement. Underlying the basement is the upper crustal material extending to Conrad discontinuity at depth of about 18 to 26 km. Earth materials below the Conrad discontinuity constitutes of the lower crustal material overlying the border of upper mantle at depth of 33 to 42 km representing the Mohorovicic discontinuity.